Modernization Of The Production Biotery Of The Instituto Nacional De Higiene “Rafael Rangel (inhrr) - Moya-Acosta, Manuel; Esteves-Guerra, Carmen; Sifones-Díaz, Freddy; Fernández, Rafael (Spei Domus, 2020)
Introduction: Animal use in biomedical investigations and in reactive production requires that these are kept under standardized conditions, following strict international regulations, guarantying: reliable, reproducible and comparable results. THE INHRR Laboratory animal center, had faults in its infrastructure, equipment that had ended their useful life, with a deficient maintenance and faulty reposition that caused high levels of ammonium producing bad odor, worsen by the level of humidity surpassing 70 %.Theme: In 2016 it was decided to execute a plan for its remodeling: “Plan de Desarrollo de la Planta Física” of 1200 m2, with the purpose of adapt the installations to optimal conditions, improve the sanitary conditions, and optimize the process and flows guarantying the quality,  quantity and management of the animals used as biological substrates.Development: From the study and evaluation of possible alternatives the edification was modified in its infrastructure, terminations, service redistribution, incorporation of new cutting-edge equipment such as ventilation systems, and biosecurity, meeting COVENIN and ISO 9001:2015 standards.Conclusions: The infrastructure and the sanitary barriers which were created or modified allow a unidirectional flow for the access of clean areas and the separation of this areas with the cleaning room in this way guarantying more security in the nucleus of the foundation, in accordance with international norms for the production of laboratory animals. In this way the Laboratory Animal Center changed from a classification of microbiologic conventional animals, to: Convectional Controlled by Sanitary Barriers.
Keywords: Laboratory animals; bioterium; physical plant; remodeling